Biomass composition explains fruit relative growth rate and discriminates climacteric from non-climacteric species. (27th June 2020) - Roch, Léa; Prigent, Sylvain; Klose, Holger; Cakpo, Coffi-Belmys; Beauvoit, Bertrand; Deborde, Catherine; Fouillen, Laetitia; van Delft, Pierre; Jacob, Daniel; Usadel, Björn; Dai, Zhanwu; Génard, Michel; et al.
Abstract : A comparison of eight fruit species (herbaceous, vines, and trees) throughout their development shows that biomass composition and fruit relative growth rate are closely linked. Abstract: Fleshy fruits are very varied, whether in terms of their composition, physiology, or rate and duration of growth. To understand the mechanisms that link metabolism to phenotypes, which would help the targeting of breeding strategies, we compared eight fleshy fruit species during development and ripening. Three herbaceous (eggplant, pepper, and cucumber), three tree (apple, peach, and clementine) and two vine (kiwifruit and grape) species were selected for their diversity. Fruit fresh weight and biomass composition, including the major soluble and insoluble components, were determined throughout fruit development and ripening. Best-fitting models of fruit weight were used to estimate relative growth rate (RGR), which was significantly correlated with several biomass components, especially protein content ( R =84), stearate ( R =0.72), palmitate ( R =0.72), and lignocerate ( R =0.68). The strong link between biomass composition and RGR was further evidenced by generalized linear models that predicted RGR with R -values exceeding 0.9. Comparison of the fruit also showed that climacteric fruit (apple, peach, kiwifruit) contained more non-cellulosic cell-wall glucose and fucose, and more starch, than non-climacteric fruit. The rate of starch net accumulation was also higher in climacteric fruit. These results suggest that the way biomass is constructed has a major influence on performance, especially growth rate.